Reconstruction and Modernization of National Identity as Catalysts for Stateness: A Post-Soviet Perspective - Manukyan, Violetta (YSU Journal of International Affairs, 2025)
This article explores the processes of national identity reconstruction and modernization as pivotal drivers in the formation and consolidation of stateness in post-Soviet contexts. Drawing on comparative case studies from selected former Soviet republics, this study analyzes how national identity narratives have been rearticulated and institutionalized to strengthen state legitimacy, foster political cohesion, and enhance sovereign functionality. Methodologically, the article employs a qualitative, comparative political analysis grounded in interpretive institutionalism and constructivist approaches to identity, integrating discourse analysis of official state narratives, policy documents, and public rhetoric with process tracing of post-Soviet nation-building trajectories. The analysis highlights the interplay between historical memory, cultural policy, and state-building strategies. It argues that the modernization of national identity, when grounded in inclusive civic values and responsive governance, substantially enhances a state’s capacity to assert authority and ensure internal stability. By positioning identity not merely as a derivative of statehood but as a strategic instrument in its construction, the article contributes to a deeper understanding of the mechanisms underpinning contemporary state-building processes.
Keywords: Post-Soviet states; national identity; stateness; state-building; identity reconstruction; identity modernization